Pengaruh Metode Penilaian Pefindo terhadap Tingkat Pemeringkatan Obligasi Syariah (Sukuk) - Deanna Permata Hati; Tri Utami (Universitas Pamulang, 2020)
This study aims to obtain empirical evidence of the effect of the Pefindo Assessment Method on the Rating Level of Sharia Bonds (Sukuk). This type of research is quantitative research. The sample used was 48 data with 8 Sukuk issuing companies registered with the OJK from 2014 to 2019. The analysis techniques used in this study were classical assumption tests, panel data regression analysis, and hypothesis testing with the help of the EViews 9 program. Based on the results of this study, it can be seen that the Industrial Risk variable proxied by EBIT and the Financial Risk variable proxied by DER simultaneously affects the rating of Islamic bonds (Sukuk). Then the Industrial Risk variable which is proxied by EBIT partially influences the Sukuk rating and the Financial Risk variable which is proxied by DER partially has no effect on the Sukuk rating.Keywords: EBIT, DER, PEFINDO, Sukuk Rating